Willoughby, Blunck, and their Jewish Critics: The English Goethe Society and Anglo-German Relations in the Nazi Period. (2nd September 2021) - Wilson, W. Daniel
ABSTRACT: H. G. Fiedler and L. A. Willoughby, the most important officers of the English Goethe Society during the years 1933 to 1945, pursued the goal of peace through stronger Anglo-German ties, which led Willoughby to gestures of support for the Nazi regime. His Jewish colleague William Rose criticized him for inviting poet and Nazi literary official Hans Friedrich Blunck to an EGS reading. Willoughby then channelled his appeasement efforts into his new periodical, German Life and Letters, before abandoning rapprochement in 1937–38. Though he gave a platform to Jewish émigré writers in PEGS before and after the war, and broke with the revanchist writer Hans Grimm, he supported Blunck's denazification and positively reviewed Blunck's untrustworthy memoirs.